CRITICAL DISCOURSE ANALYSIS OF SAMBAL ABC ADVERTISEMENT: A THREE-DIMENSIONAL FRAMEWORK APPROACH - Ni Made Wersi Murtini (Jurnal Santiaji Pendidikan (JSP), 2026)
This research delves into the critical discourse analysis (CDA) of an advertisement for Sambal ABC, an Indonesian chili sauce product, employing Fairclough’s three-dimensional framework. It explores the linguistic, discursive, and social dimensions prevalent in advertising language. The study contextualizes advertising as a form of discourse aiming to influence consumer attitudes and behaviors, emphasizing the relevance of CDA in decoding cultural nuances embedded within advertising. Methodologically, a qualitative approach was employed, focusing on linguistic analysis of pronouns, imperatives, and adjectives. Additionally, the study investigated textual practice which focuses on the linguistics element, discursive practices which is unveiling how language production and consumption influence discourse formation; moreover, sociolinguistic analysis emphasized socio-historical factors affecting discourse interpretation. Results from the critical analysis of the Sambal ABC advertisement revealed deliberate linguistic choices aiming at audience engagement. Pronouns personalized the message, imperatives directed actions, and adjectives highlighted desired qualities, enhancing the advertisement’s appeal. Discursively, the advertisement positioned the audience as active participants, emphasized product uniqueness, and promoted social responsibility towards farmers, establishing an emotional connection rooted in family values. The study’s societal implications were evident, challenging norms of expressing gratitude towards products, recognizing farmers’ contributions, and tapping into cultural identity. This research underscores the intricate interplay between language, persuasion, and societal contexts within advertising, emphasizing the need for understanding discourse in advertising as a powerful tool shaping consumer perceptions.